A Study on Prevalence of Anemia, Etiological Factors and Hemato-biochemical Alterations in Anaemic Goats in Goat Research Station, Burnihat, Assam - Patowary, Prerona; Bhuyan, Dipak; Das, Arpana; Devi, Pallabi; Hazorika, Mousumi; Deka, Abhijit; Lahkar, Deepa; Changkija, Bendangla; Kalita, Manoj Kumar (International Journal of Bio-resource and Stress Management, 2026)
The present study was carried out from March, 2025 to February, 2026 at Goat Research Station, Burnihat, Assam, India to assess the incidence and etiological factors including haemato-biochemical changes associated with anemia in goats. Among the total of 220 goats examined for anemia, 150 (68.18%) goats were found to be anaemic. The incidence of anemia was higher in females (61.33%) compared to males (38.66%). The incidence of anemia was higher in goats of less than 1 year of age (65.33%) compared to those of more than 1 year of age (34.66%). The seasonal incidence was higher in the monsoon season (53.33%) followed by summer (26.66%) and winter (20%). The results of the etiological study showed that the highest incidence was recorded for mixed endoparasitic infestation (54.00%), followed by hemo-protozoan infection (18.66%), tick infestation (16.66%), coccidiosis (6.66%), and other etiological factors such as aging, nutritional factors, etc. (4%). The results of the haemato-biochemical study showed that the values of TEC, Hb, PCV, MCV, MCH and MCHC were significantly (p<0.05) decreased in anaemic goats compared with the healthy ones. The values of TLC and neutrophils were significantly (p<0.05) increased in anaemic goats compared with the healthy ones. The values of total protein and albumin were significantly (p<0.05) decreased in anaemic goats compared with the healthy ones. These findings emphasized the need for timely diagnosis, improved management practices, strategic deworming, and nutritional supplementation to reduce anemia prevalence and enhanced overall health and productivity in goats significantly.